2010
DOI: 10.1007/s00216-010-3838-x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of cancerous and non-cancerous cell lines by headspace-analysis with PTR-MS

Abstract: Proton transfer reaction mass spectrometry (PTR-MS) has been used to analyze the volatile organic compounds (VOCs) emitted by in-vitro cultured human cells. For this purpose, two pairs of cancerous and non-cancerous human cell lines were selected:1. lung epithelium cells A-549 and retinal pigment epithelium cells hTERT-RPE1, cultured in different growth media; and 2. squamous lung carcinoma cells EPLC and immortalized human bronchial epithelial cells BEAS2B, cultured in identical growth medium. The VOCs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…After applying LDA with backward removal (p < 0.05) of variables, only two VOCs proved to be significant for discrimination between three defined previously, namely 1,2,4-trimethylbenzene and benzaldehyde. These compounds have been already identified in cancer cell studies by Brunner et al 29. using PTR-MS, by Filipiak et al 16.…”
Section: Resultsmentioning
confidence: 86%
“…After applying LDA with backward removal (p < 0.05) of variables, only two VOCs proved to be significant for discrimination between three defined previously, namely 1,2,4-trimethylbenzene and benzaldehyde. These compounds have been already identified in cancer cell studies by Brunner et al 29. using PTR-MS, by Filipiak et al 16.…”
Section: Resultsmentioning
confidence: 86%
“…Results of studying different lung cancer cell lines in 2D cultures suggested that altered VOC production can be detected in the early stages of carcinogenesis, and can represent a basis for noninvasive diagnosis of lung cancer. Therefore, 2D studies on various normal or cancer cell lines showed either an increase or decrease in several volatile compounds classes such as alkanes, aldehydes, aromatic compounds or alcohols [25, [165][166][167][168][169][170][171][172]. A recent study uses both cancerous and noncancerous lung cell lines grown in 3D scaffolds of collagen type I hydrogel [167].…”
Section: In Vitromentioning
confidence: 98%
“…Thus, the VOC profiles under cytotoxic exposure were measured. Polyphyllin belongs to the antimitotic class of agents which can promote tubulin polymerization and is now widely used to treat a range of malignancies (19)(20)(21). Vitamin C was also included in this study as a positive control compound as it is always used in chemotherapy for its antioxidant (22,23).…”
Section: Polyphyllin Effects On the Vocs Metabolism Of Tumor Cell Linesmentioning
confidence: 99%
“…However, it should be collocated with electrosurgical devices and measuring it production of "smoke", which means characterization can't be made unless the electrosurgical knife has cut down. Proton transfer reaction mass spectrometry (PTR-MS) was also carried out for online and offline characterization of VOC biomarkers from cancer cells [19]. Nevertheless, the detected VOC biomarkers were limited to molecules with a proton affinity greater than that of water [20], among which there were not extremely specific cancer-related VOCs observed by the online measurement of PTR-MS.…”
Section: Introductionmentioning
confidence: 99%